Experimental Investigation of Condensation Heat Transfer on Vertical Hydrophilic-Hydrophobic Aluminium Surfaces - Pouyan Mohseni Behbahani; GhanbarAli Sheikhzadeh (Journal of Heat and Mass Transfer Research, 2022)
Condensation is an important heat transfer regime, with vast applications in industries such as power generation and cooling systems. In the present study, the changes in the coating thickness and geometry of hydrophobic areas were investigated on hydrophobic-hydrophilic plates and totally hydrophobic ones, and a no-coating plate was also studied experimentally for the condensation phenomenon. Considering the use of aluminium as the base material, tests such as lithography with positive photoresist was conducted to study the photoresist adhesion to the aluminium surface and its impact on heat transfer, as well as testing the lift-off process to remove the remaining photoresist at the final stage of producing the plates, to improve their surfaces and optimize the major parameters in the production stage. For this study, one type of totally hydrophobic surface and two types of hybrid hydrophobic-hydrophilic surfaces with different widths of hydrophobic and hydrophilic areas were produced, each type in three thicknesses of 200, 450 and 900 nm. Considering the different values of coating thicknesses, the width of the hydrophobic and hydrophilic areas, the heat transfer coefficient and heat flux were calculated for each plate, and the optimal conditions for each plate were determined. Compared to the uncoated plates, the heat transfer coefficient and heat flux for each plate with hybrid hydrophobic-hydrophilic surfaces (width of 860 μm for hydrophilic area and 970 μm for the hydrophobic, and thickness of 450 nm) registered increase by 1.44-2.01 and 1.43-1.81 times, respectively, which were the highest among the plates in the present study.